Pengaruh Aktivitas Penambangan Pasir terhadap Kualitas Air Sungai Lemo Kelurahan Nambo Kota Kendari - Prahara, Teguh Candra; Ndibale, Wa; Ilham, Ilham (Universitas Muhammadiyah Kendari, 2022)
Along with the times, the industry in Indonesia is getting higher, especially the industry in the mining sector. Exploitation of mineral resources or minerals such as sand mining is one of the supporters of the development sector both physically, economically and socially. This study aims: (1) to find out the sand mining activities in the Lemo river body in Nambo Village, (2) to determine the effect of sand mining activities on the quality of pH, TSS, brightness, and water temperature in the Lemo river. The results of the analysis of the Lemo river water sample at the Environmental Engineering laboratory, Faculty of Engineering, Muhammadiyah Kendari University, showed that the pH value of the sample point 1 was 7.3, sample II was 7.0 and sample III was 6.9. The TSS level in sample I was 393.33 mg/L, sample II was 8750 mg/L, and sample III was 8990 mg/L. The value of the brightness level of sample I is >2 m, sample II is <1 m and the brightness level of sample III is at a depth of <1 m. While for the temperature test for sample I, the water temperature is 23°C and the air temperature is 25°C, sample II is the water temperature is 27°C and the air temperature is 25°C, while for the third sample, the water temperature is 26°C and the air temperature is 24° C with each deviation of ± 3.